(untitled) (Research, Society and Development, 2021)
Objective: to analyze the leadership of nursing students based on Schoenstatt’s pedagogy. Method: qualitative research, developed through action research in a higher education institution in southern Brazil, with six academics from the seventh semester of undergraduate nursing, through a semi-structured questionnaire, analyzed through discursive textual analysis. Results and discussion: six female academics participated in the research, all female, aged between 23 and 33 years old, all of whom had already come into contact with some material on leadership, from which they had a previously elaborated concept. From the data analysis, two categories emerged, described below: love and trust as essential characteristics of a leader; self-knowledge as a tool in the leadership development process. Final considerations: the elements that make up Schoenstatt’s pedagogy addressed in this study contribute to the academic training of nurse leaders in view of the current demands of health services and promote training that signals the perspectives of being a leader.